The Edinburgh companion to literature and sound studies - Groth, Helen; Murphet, Julian (Edinburgh : Edinburgh University Press, 2024)
This field-defining collection maps key intersections between sound studies and literary studiesProvides a unique focus on literary applications of sound studies researchFeatures a wide range of international, emergent and established scholarsInterdisciplinary work throughoutConsiders a broad range of historical periodsFeatures entirely new commissioned work; no republished material available elsewhere is includedCollections on sound studies have seldom explored the vexed relationship between literature - a medium largely defined by its silence - and the dynamics and technologies of sound. This Companion is designed to help sound studies scholars grapple with the auditory capacities of text and encourage literary scholars to take full cognisance of the rich soundscapes mapped, or created, by texts read quietly. The essays assembled here consider a broad range of sound studies topics, including music in writing; the inscription of listening; worlding through sound; military and industrial noise; the gender of sound; racialised soundscapes; theatrical sounds; literature and sound media; and sonic epistemology. Helen Groth and Julian Murphet present a comprehensive set of new research on the relationship between sound and writing over time from a range of eminent, established and emerging sound studies scholars.
The sound a sentence makes : on poetry, judgement, and hearing / Astrid Lorange -- The limits of listening : riotous women, imperial structures, and sonic archives / Helen Groth -- Piano/Forte : writing audible space, Jane Austen, Dorothy Richardson, and others / David Toop -- Oralities, literacies, and the xenophobic fallacy / Richard Cullen Rath -- Notes to literature : scores as musical reproduction in the literary text / Tamlyn Avery -- Sound agonistes : music and the economy of sacrifice in sound studies / Miranda Stanyon -- Shakespeare's vibrant theatres / Bruce R. Smith -- 'Imaginative and musical mixtures of sounds' : rap, patter, and hyper diction in musical theatre / Tamsen O. Wolff -- 'Let it resound' : 'Lift every voice and sing' as sonic witness / Noelle Morissette -- Sound media, race, and voice / Sam Halliday -- The acousmatics of prison writing / Julian Murphet -- Aural anxiety and rurality in women's Second World War writing / Imogen Free -- Sound technology and US fiction in the postwar era : the ethics and aesthetics of cross-racial listening / K.C. Harrison -- Coded sound : reading in the age of networked media / Justin St. Clair -- Media affordances of literary audio : interrelations of format and form -- Oh-ee-oh-ee-oh-ee-aw-ee-aw! : Sound descriptors in the books of Tarzan as facilitators of presence / Mark Grimshaw-Aagaard -- An auditory history of early modernity : listening to Enlightenment and industry in Britain, 1700-1900 / Peter Denney -- 'This is/not was' : the violence of circulation and the sonics of submerged language / Andrew Brooks -- Shriek and hum : industrial noise and productivity / David Ellison -- A critical poetics of warfare / Mark Byron -- The Great War : sonic fragments in literature and sound studies / Michael Bull -- Sonic epistemologies / Holger Schulze -- The cultural poetics of a buoyancy sound from Amazonian Ecuador / Janis Nuckolls -- Havoc ornithologies / Jody Berland.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (JSTOR, viewed on March 07, 2024).
JSTOR
Keywords: Sound in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh